2016
DOI: 10.18632/oncotarget.12307
|View full text |Cite
|
Sign up to set email alerts
|

The natural compound sulforaphene, as a novel anticancer reagent, targeting PI3K-AKT signaling pathway in lung cancer

Abstract: Lung cancer is one of the leading causes of cancer death worldwide. Isothiocyanates from cruciferous vegetables been shown to possess anticarcinogenic activities in lung malignances. We previously found sulforaphene (4-methylsufinyl-3-butenyl isothiocyanate, SFE), one new kind of isothiocyanates, existing in a relative high abundance in radish seeds. An efficient methodology based on macroporous resin and preparative high-performance liquid chromatography was developed to isolate SFE in reasonably large quanti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 31 publications
2
30
0
Order By: Relevance
“…These results suggest that the PSC-hex components disrupt multiple tumoral signaling pathways, including growth arrest (associated to proteins p21 and p53) and/or apoptosis pathways (associated to proteins Bax, Bcl-2 and p53). These results are in line with recent findings, showed that many natural compounds found in mushrooms have pro-apoptotic activities (Yang et al, 2016). Moreover, literature supports that mushroom constituents such as sterols may contribute to the antitumoral effects observed in this study (Heleno et al, 2015).…”
Section: Psc Extract Exhibited Anti-proliferative Activity Against Thsupporting
confidence: 93%
“…These results suggest that the PSC-hex components disrupt multiple tumoral signaling pathways, including growth arrest (associated to proteins p21 and p53) and/or apoptosis pathways (associated to proteins Bax, Bcl-2 and p53). These results are in line with recent findings, showed that many natural compounds found in mushrooms have pro-apoptotic activities (Yang et al, 2016). Moreover, literature supports that mushroom constituents such as sterols may contribute to the antitumoral effects observed in this study (Heleno et al, 2015).…”
Section: Psc Extract Exhibited Anti-proliferative Activity Against Thsupporting
confidence: 93%
“…Intra venous injection of the pro-enzymes resulted in maximum detectable levels in plasma at 15–30 min that decline in the first hour and were still present in low levels after three hours post-dose. These observations are similar to time-concentration profiles found in previous pharmacokinetic studies with potential therapeutic agents for human cancers, including pancreas 37 , 38 and also in current chemotherapeutics used in the clinic such as gemcitabine 39 . Moreover, examination of the tissue distribution demonstrated that proenzymes perfused into organs, including the heart, liver, spleen, lung, kidney and entire gastrointestinal tract which indicated a wide tissue distribution of the pro-enzymes 40 .…”
Section: Discussionsupporting
confidence: 88%
“…Naturally occurring dietary compounds have increased the interest in the prevention of various types of cancers (14)(15)(16), including lung cancer (17)(18)(19)(20). Cucurbitacin is commonly found in the cucurbitaceae family and has been used in traditional medicine (21).…”
Section: Introductionmentioning
confidence: 99%